(untitled) (International Journal of Innovative Technologies in Economy, 2020)
One of the main trends of modern economic relations is the transition of priorities from the producer market to the buyer market. In this regard, the ability to combine production, the planning system with individual purchasing preferences is becoming a decisive factor in competition and the economy of the future. As a result, rapid changes in buyers’ preferences, their requests for quality of delivery lead to the need to reduce delivery times and volumes, and to reduce reserve stocks of time and materials. Perhaps the second feature is the strengthening of integration processes among countries, particularly in the context of the expansion of the WTO, with the possibility of placing production in countries with cheaper labor and lower tax rates, and the development of international trade has opened up access to cheaper resources.